TRADISI BERDOA UNTUK KENDARAAN BARU DI DUSUN SIALANG GATAP DAN DARUSSALAM LABUHAN BATU UTARA - Ghoni, Abdul; Muhammad Nuh Siregar (Qolamuna : Jurnal Studi Islam, 2024)
Customs in society usually come from previos generation who have been practicing them forgenerations. The tradition of praying on new vehiclesin the hamlets of Sialang Gatap and  Darussalam has been caried out for a long time. Local people often call is the Topung Tawar. We are allowed to carry out a tradition if it is in accordance with religiouslawa, namely based on two main guidelines, namely the Quran dan Hadith. This social phenomenon is studied and resesarched using living hadith resesarched, namely the application of hadith to tradition, customs of ther communities. Then we will look for brights spots from events in the field by adapting to the hadith of the propet Muhammad. Keywords : Tradition, Topung Tawar, Living Hadith